Construction quality management - Yemelianova, О.; Tytok, V. (Ways to Improve Construction Efficiency, 2019)
Improving the quality of construction products is a natural process that reflects the objective trend in the development of social production. It is due to the essence of market relations, considering quality as the main measure in the general perception of supply. A significant impetus to this process is given by quality management, which directs participants in the construction industry to create products that meet all the requirements. The right choice of management methods and tools enables successful implementation of projects, which in turn directly affects their competitiveness. The quality of construction products, as well as the quality of building (finishing) materials, as well as construction technologies, including design and other engineering solutions, should be much higher than the average formed. The most important function of quality management of construction products is to encourage construction industry participants to improve the quality characteristics of the products created. The managerial influence not only promotes high quality construction, but also adequately responds to all developments in the investment and construction sphere: organizational, structural, financial, technical and other changes. The article considers such a parameter of the project as quality, compares the experience of implementing the quality management system in domestic construction organizations and construction organizations of some foreign countries. The focus is on the most common methods and programs aimed at improving product quality. A study of domestic and foreign quality management and control systems has shown that the quality management and control system in foreign countries is organized more clearly and effectively than in our country, and certainly positive experience should be taken into service by our construction (and not only) companies, which is only to increase their competitiveness. As a result, the winners will be all participants of the construction project: the consumer of the end result, the customer-developer, investor, insurance companies, authorities and others.